The Causal Relationship Model Between Quality of Working Life and Organizational Culture the affect Organizational Commitment of Supporting Staffs of Rajamangala University of Technology Krungthep - Jantasang, Sakchai (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
This research aimed to: 1) examine the relationship of the developed model with empirical data; and 2) develop the causal relationship model between quality of working life and organizational culture the affect organizational commitment of supporting staffs of Rajamangala University of Technology Krungthep. The sample was 210 supporting staff of Rajamangala University of Technology Krungthep derived by convenience sampling. Data were collected by an online questionnaire with Google Form and the casual relationship was examined by LISREL. The research results were as follows: 1) The causal relationship model between quality of working life and organizational culture the affect organizational commitment of supporting staffs of Rajamangala University of Technology Krungthep was consistent with the empirical data with goodness of fit statistics: chi-square test = 55.28, df=42, p-value=.08, GFI=.98, AGFI=.98, SRMR=.01, RMSEA=.02 and 2) quality of working life has positive direct effect and indirect effect on organizational commitment by organizational culture as mediator and organizational culture has positive direct effect on the organizational commitment. All variables in the model can explain 78 % of the variance of the organizational commitment of the supporting staffs. Article history: Received 19 September 2022 Revised 16 April 2023 Accepted 17 April 2023 SIMILARITY INDEX = 5.39 %